2007
DOI: 10.1002/cncr.22395
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of nonvisceral soft tissue leiomyosarcoma in 225 patients from the Scandinavian Sarcoma Group

Abstract: BACKGROUND.Leiomyosarcoma of nonvisceral soft tissues is an uncommon malignant tumor; thus, only small numbers of cases have been reported. This study was based on a large series of patients from the Scandinavian Sarcoma Group Register acquired during a 15‐year period (from 1986 to 2001). Follow‐up information was available for all patients.METHODS.The authors analyzed the clinical features of 225 patients with cutaneous, subcutaneous, or deep‐seated leiomyosarcoma of the extremities, trunk wall, and superfici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
3
14

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(156 citation statements)
references
References 39 publications
6
133
3
14
Order By: Relevance
“…There has been sometimes a quest for more accurate prediction (eg, plotting mitotic rate with recurrences/ metastases), but very small sample size in most series of soft tissue leiomyosarcomas has hampered The largest recent series from the Scandinavian Sarcoma Group showed a metastatic rate of 20% for subcutaneous and 60% for deep intramuscular leiomyosarcomas. 42 Tumors with lower mitotic rates may show longer recurrence-free survivals. Disruption of tumor (previous partial surgery) was found an adverse factor in one series.…”
Section: Leiomyosarcoma Of Peripheral Soft Tissuementioning
confidence: 99%
“…There has been sometimes a quest for more accurate prediction (eg, plotting mitotic rate with recurrences/ metastases), but very small sample size in most series of soft tissue leiomyosarcomas has hampered The largest recent series from the Scandinavian Sarcoma Group showed a metastatic rate of 20% for subcutaneous and 60% for deep intramuscular leiomyosarcomas. 42 Tumors with lower mitotic rates may show longer recurrence-free survivals. Disruption of tumor (previous partial surgery) was found an adverse factor in one series.…”
Section: Leiomyosarcoma Of Peripheral Soft Tissuementioning
confidence: 99%
“…Vascular LMS is a rare tumor origin the media of vessel walls, low extremities veins are the most commonly veins affected, furthermore, the popliteal and tibial veins even less frequently, some few cases have been published [1,[4][5][6] . The diagnostic of leiomyosarcoma, it must first be distinguished from other types of tumors, that differentiate these tumors from other soft tissue sarcomas it's not easy to do, a good histological and immunohistochemical study using markers are useful for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Dzsinich et al (1992) [5] reported on 13 cases of vascular LMS, which 8/13 arose from the inferior cava vein 2/13 from the iliac vein, and 2/13 cases from the saphenous vein. Svarvar et al (2007) [6] reported on 225 patients with LMS of all types from the Scandinavian Sarcoma Group with a cumulative survival of 49% at 10 years. The tumours in Berlin's series (1984) [8] were located in the superficial femoral vein in 3 patients, in the great saphenous vein in one case, in the popliteal vein in one case, and in the axillary vein in one case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations